Analisis Kinerja Laporan Keuangan dari Perspektif Manajemen dan Pemilik PT. Mega Perintis Tbk Periode 2022-2024 - Elsi Novita Sary; Deshy Shilvana; Riskia Ramadhani (Al-Manar Journal of Accountancy and Business Studies, 2025)
This study aims to analyze the financial performance of PT. Mega Perintis Tbk for the period 2022 to 2024 from the perspective of the owner. Data were collected by accessing the company's official website www.megaperintis.com and the Indonesia Stock Exchange website (www.idx.co.id) to obtain audited annual financial reports for the 2022 to 2024 period. The data were analyzed using a quantitative approach with financial ratio calculations, including liquidity ratios, solvency ratios, activity ratios, and profitability ratios. The results show that the company's liquidity ratio decreased in 2022 but improved in 2023 and 2024, reflecting the company's ability to meet its short-term obligations. The solvency ratio remained relatively stable, indicating the company's ability to maintain a healthy capital structure. In terms of activity, there was an increase in asset turnover efficiency in 2023 and 2024. Meanwhile, the profitability ratio showed fluctuations but recorded a positive trend towards the end of the period. These findings reflect the company's efforts to improve financial performance and its ability to adapt to changing market conditions. This study is expected to provide useful information for the company’s owners and other relevant stakeholders in making financial decisions and formulating future business strategies.